Adsorption heat pump optimization by experimental design and response surface methodology. (25th June 2018) - Pinheiro, Joana M.; Salústio, Sérgio; Valente, Anabela A.; Silva, Carlos M.
Graphical abstract: Highlights: Study of X and Y zeolites with/without binder for adsorption heat pumps (AHPs) Results from Box-Behnken design and response surface methodology (DoE/RSM) analyzed. Studied variables: bed thickness, time, condenser and heat source temperatures. The binder in the 13X formulation does not penalize AHP performance significantly. DoE/RSM aid efficient optimization of AHP design and control. Abstract: The performance of commercial zeolites, with and without binder in its formulation (SYLOBEAD® MS C 548: 13X with binder; Köstrolith® 13XBFK and NaYBFK: 13X and NaY without binder, respectively), for water adsorption heating applications was compared in this work. Accounting for a Box-Behnken design with four factors (time of adsorption and desorption, t ADS + DES ; condensation temperature, T cond ; heat source temperature, T HTF, hot ; bed thickness, δ ) and three levels, a set of 25 simulations per adsorbent was accomplished, and the performance of the adsorption units was evaluated through the coefficient of performance ( COP ) and the specific heating power ( SHP ). The results suggested that the presence of the binder in the formulation of 13X does not penalize the zeolite performance significantly, and that NaYBFK is the most promising material. For the latter solid, statistical outcomes were analyzed and insights about their usefulness to optimize the design and operation of adsorption heat pumps are provided. Pareto charts displaying the impact ranking of the factors upon COP and SHP are discussed, and simple equations are provided for the expeditious estimation of both indicators. Such models were utilized to map system performance and to select optimal geometric/operating parameters that meet specific performance requirements.